Fluorine-Substituted Phenanthro[9,10-d]imidazole Derivatives with Optimized Charge-Transfer Characteristics for Efficient Deep-Blue Emitters - Li, Zhiqiang; Xie, Ning; Xu, Yincai; Li, Chenglong; Mu, Xiaoyue; Wang, Yue (Organic Materials, 2020)
The development of high-efficiency deep-blue emitters is of great importance for full-color organic light-emitting diodes (OLEDs). In this contribution, three difluorine-substituted phenanthro[9,10-d]imidazole derivatives with optimized charge-transfer character and deep-blue emission have been developed. It is demonstrated that the fluorine substitution can facilitate the “state mixing” of singlet and triplet excitons, which increases the utilization of triplet excitons. The fluorine substitution also brings more intermolecular interactions which have influence on the molecular packing pattern of the solid states, ultimately impacting their carrier mobilities. Through fine-tuning of molecular structures, 4'-(1-(3,5-difluorophenyl)-1H-phenanthro[9,10-d]imidazol-2-yl)-N,N-diphenyl-[1,1'-biphenyl]-4-amine (2FPPIDPA) realized a high exciton utilization ratio with Commission Internationale de L'Eclairage (CIE) coordinates of (0.156, 0.046), and 4'-(1-(3,5-difluorophenyl)-1H-phenanthro[9,10-d]imidazol-2-yl)-N,N-diphenyl-[1,1'-biphenyl]-4-amine (2FPPIDPA) achieved an external quantum efficiency of 8.47% with CIE coordinates of (0.152, 0.083) in multilayer OLEDs. Due to their good hole-transport abilities, double-layer OLEDs without the hole-transport layer showed performances comparable or even superior to the multilayer ones.
Keywords: organic light-emitting diodes; blue emitters; phenanthro[9; 10-d]imidazole; charge-transfer state; fluorine substituents